Зависимость параметров зоны низких сейсмических скоростей от минерального состава пород Украинского щита в различных РГ-условиях эксперимента - Карнаухова, Е.Е. (Геоінформатика, 2015)
На основе детального петрографического анализа основных петротипов изверженных и метаморфических пород Украинского щита, обобщения имеющейся геолого-геофизической информации о структурно-тектоническом положении и особенностях формирования районов развития исследуемых пород, а также по данным экспериментальных исследований упругих параметров при высоких давлениях и температуре определена степень влияния минерального состава пород щита на проявление зон низких сейсмических скоростей. В ходе исследований получены статистически обоснованные корреляционные зависимости скорость—минеральный состав для различных глубин. Установлено, что в зонах низких скоростей влияние минерального состава на упругие параметры пород невысокое и значительно слабее влияния структурного преобразования пород. На основі детального петрографічного аналізу основних петротипів вивержених і метаморфічних порід Українського щита, узагальнення наявної геолого-геофізичної інформації про структурно-тектонічне положення і особливості формування районів розвитку досліджуваних порід, а також за даними експериментальних досліджень пружних параметрів за високих тиску і температури визначено ступінь впливу мінерального складу порід щита на прояв зон низьких сейсмічних швидкостей. У ході досліджень отримано статистично обґрунтовані кореляційні залежності швидкість—мінеральний склад для різних глибин. Установлено, що в зонах низьких швидкостей вплив мінерального складу на пружні параметри порід невисокий і значно менший за вплив структурного перетворення порід. Purpose. The purpose of the article is to conduct experimental studies of low velocity zone (LVZ) parameter dependences on the mineral content of Ukrainian Shield rocks in the programmed PT-conditions.
Design/methodology/approach. To solve the problem a method of multidimensional correlation-regression analysis was used, together with the explosion seismology data. The results obtained are presented as descriptive statistics, histograms, schedules, linear pair and plural cross-correlation dependences. Originally, the regional collection of rocks was preliminarily studied in laboratory conditions at atmospheric pressure and room temperature. The petrographic analysis was carried out.
The most representative samples were investigated at hydrostatic pressure up to 0,5-0,6 Gpa. After this information, was statistically processed, we selected groups of samples which were studied under the simultaneous P and T effect. In these studies, P and T were changed according to the PT-program of possible regional change of these parameters with depth. According to the conditions of the experiment, a rock sample was supposed to “plunge” gradually to the preset depth and simultaneous measurements of the Vр, Vs were made and the volume decrement was measured.
Findings. The experiments show that the Vp, Vs = ƒ(PT) = ƒ(Н) dependences have complicated regularities: on the curves show velocity inversion zones with maxima and minima manifestation. Inversion zones change their width with depth (ΔН) and decrease the velocity maximally (ΔVp). Here the rocks are characterized by low Young and shear modules, high brittleness (low Poisson’s ratio), high discompaction (high dilatancy), and low thermal conductivity (λ). The inversion zones established by laboratory experiments in most cases are in good agreement with LVZ in the Earth's crust from DSS profiles. For the most selected groups of rocks ΔVp is 0,02-0,16 km/s; ΔH is in the depths interval of 6-20 km. In all the rock groups, elastic parameters dependences on the percentage content of rock-forming minerals tend to decline depth. In LVZ the influence of the mineral composition on elastic parameters is low and considerably less than structural transformations of rocks.
Practical value/implications. The obtained experimental and statistically treated data of a broad spectrum of Ukrainian Shield rocks may be used for petrophysical crustal modeling, enabling us to predict the content and state of the Earth’s crust mineral matter.